New neuroretinal rim blood flow evaluation method combining Heidelberg retina flowmetry and tomography. Issue 3 (1st March 2001) - Jonescu-Cuypers, Christian P; Chung, Hak S; Kagemann, Larry; Ishii, Yoko; Zarfati, Drora; Harris, Alon
Abstract : AIM: Accurate Heidelberg retina flowmeter (HRF) measurements require correct manual setting of the HRF photodetector sensitivity. The neuroretinal rim produces a weak signal relative to the peripapillary retina. A newly developed HRF alignment and sensitivity protocol, capable of accurate rim measurement, was investigated. METHODS: 18 eyes of nine healthy volunteers were examined by HRF. Three images of each eye were taken using three different imaging methods. Method 1: a conventional image (optic nerve head centred image with photodetector sensitivity optimised for the strong signal from the peripapillary retina); method 2: the setting of method 1 with photodetector sensitivity optimised for the weak signal from the rim; and method 3: the setting of method 2 with the temporal rim margin tangent to the lateral image border to remove the overpowering signal from the temporal peripapillary retina. The neuroretinal rim was defined by the Heidelberg retina tomograph (HRT). Blood flow and reflectivity values (DC component) in the rim area were compared for the three methods using pointwise analysis. Coefficients of variation of repeated measurements in 12 subjects have been calculated for method 3. RESULTS: The neuroretinal rim area measured by method 1 had a significantly lower brightness compared with method 2 and 3 (p=0.0002 and p=0.0002, respectively). Method 2 provided proper sensitivity for the weak signals of the rim area based on rim tissue DC values; however, this sensitivity setting was too high for the strong signal from the peripapillary retina. Method 3 avoided the strong peripapillary signal with the proper signal from the rim and provided significantly higher flow values of the rim area at 75 and 90 percentile pixels (p=0.0065 and p=0.0038 respectively) compared with method 2. Interobserver repeatability ranged from 16.85% to 21.96% for the different parameters. CONCLUSIONS: Method 3 provides an accurate and reproducible flow measurement of the neuroretinal rim area through proper sensitivity for the weak rim signal, alignment, and removal of the strong temporal signal from the image. This new method is recommended to improve accuracy of blood flow measurement in the neuroretinal rim.